2017
DOI: 10.1073/pnas.1618354114
|View full text |Cite
|
Sign up to set email alerts
|

Putative transmembrane transporter modulates higher-level aggression in Drosophila

Abstract: By selection of winners of dyadic fights for 35 generations, we have generated a hyperaggressive Bully line of flies that almost always win fights against the parental wild-type Canton-S stock. Maintenance of the Bully phenotype is temperature dependent during development, with the phenotype lost when flies are reared at 19 °C. No similar effect is seen with the parent line. This difference allowed us to carry out RNA-seq experiments and identify a limited number of genes that are differentially expressed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…D. melanogaster displays a gender-specific repertoire of stereotyped aggressive behaviors, which provides a feasible model for investigating the genetic and neural basis of aggression 22,23 . Although substantial studies have shown that aggression is shaped by genetic and environmental factors, it is observed that high heterogeneity of aggressive manifestation exists among individuals, and the root cause of this heterogeneity is relatively unclear, with interactions among hosts, microbiome and environment usually offered as possible explanations 24 . In the wild, Drosophila mainly feeds on decaying fruits that are inhabited by a myriad of microbes 25 .…”
mentioning
confidence: 99%
“…D. melanogaster displays a gender-specific repertoire of stereotyped aggressive behaviors, which provides a feasible model for investigating the genetic and neural basis of aggression 22,23 . Although substantial studies have shown that aggression is shaped by genetic and environmental factors, it is observed that high heterogeneity of aggressive manifestation exists among individuals, and the root cause of this heterogeneity is relatively unclear, with interactions among hosts, microbiome and environment usually offered as possible explanations 24 . In the wild, Drosophila mainly feeds on decaying fruits that are inhabited by a myriad of microbes 25 .…”
mentioning
confidence: 99%
“…Our focal flies were descendants of wild‐caught D. melanogaster captured in several sites in Southern Ontario in summer 2014 and kept in a large, outbred laboratory population (Baxter & Dukas, ). In all of the experiments, focal males of the aggression treatment interacted with males from a hyperaggressive line generated via artificial selection and inbreeding in the Kravitz laboratory at Harvard University (Chowdhury, Chan, & Kravitz, ; Penn, Zito, & Kravitz, ). We used the hyperaggressive males as the stimulus flies to ensure that we had sufficient levels of aggression in all the experimental arenas.…”
Section: Methodsmentioning
confidence: 99%
“…Why some fights progress to high intensity levels, while others do not, is still not fully understood. Genetics undoubtedly plays a role as multiple genes have been found to be associated with control of aggression (Chowdhury et al, 2017;Edwards et al, 2009;Shorter et al, 2015). Males also can be bred to be hyperaggressive 'bullies' that almost always win fights against genetic background controls, and that commonly display high intensity behaviors such as boxing (Dierick and Greenspan, 2006;Penn et al, 2010).…”
Section: Introductionmentioning
confidence: 99%